2022
DOI: 10.3390/jof9010064
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Reveals Candidate Genes Related to Stipe Gradient Elongation of Flammulina filiformis

Abstract: Stipe gradient elongation is an important and remarkable feature in the development of most mushroom fruiting bodies. However, its molecular mechanism has rarely been described. Here, the decreasing trend of stipe elongation and increasing trend of cell length in a gradient from the top to the base of the stipe were determined in a model basidiomycete mushroom: Flammulina filiformis. According to RNA-seq results, 1409 differentially expressed genes (DEGs) were identified among elongation region (ER), transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Previous investigations found that the analysis of DEGs offered valuable information regarding the development of the fruiting body. This process is initiated by a stimulus that activates particular genes responsible for the transformation of mycelium into a fruiting body ( Yu et al, 2012 ; Muraguchi et al, 2015 ; Song, Kim & Kim, 2018 ; Yan et al, 2023 ). To identify the specific unigenes that contribute to the development of fruiting bodies in L. decastes , we conducted an analysis of the gene expression profiles across different comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations found that the analysis of DEGs offered valuable information regarding the development of the fruiting body. This process is initiated by a stimulus that activates particular genes responsible for the transformation of mycelium into a fruiting body ( Yu et al, 2012 ; Muraguchi et al, 2015 ; Song, Kim & Kim, 2018 ; Yan et al, 2023 ). To identify the specific unigenes that contribute to the development of fruiting bodies in L. decastes , we conducted an analysis of the gene expression profiles across different comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al described a special link of spermidine and lysine which was probably involved in the development of mushroom fruiting body and in response to the multiple environmental factors [8]. Another study corroborated the longchain fatty acid synthesis pathway which was responsible for stipe gradient elongation in F. filiformis [9]. Gong et al offered a novel strategy of Hypsizygus marmoreus cultivation using vernalization-like low-temperature fruiting [10].…”
mentioning
confidence: 97%